\[\boxed{\text{274\ (274).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[y = f(x) - убывающая.\]
\[1)\ y = 3f(x) - убывающая,\ \]
\[так\ как\ 3 > 0.\]
\[2)\ y = \frac{1}{3}f(x) - убывающая,\ \]
\[так\ как\ \frac{1}{3} > 0.\]
\[3)\ y = - f(x) - возрастающая,\]
\[\ так\ как\ \ - 1 < 0.\ \]
\[\boxed{\text{274.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ \left\{ \begin{matrix} 2(x - 3) \leq 3x + 4(x + 1)\text{\ \ \ \ \ \ \ \ } \\ (x - 3)(x + 3) \leq (x - 4)^{2} - 1 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} 2x - 6 \leq 3x + 4x + 4\ \ \ \ \ \ \ \ \ \ \\ x^{2} - 9 \leq x^{2} - 8x + 16 - 1 \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ \ \ }\]
\[\left\{ \begin{matrix} - 5x \leq 10 \\ 8x \leq 24 \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ \ }\left\{ \begin{matrix} x \geq - 2 \\ x \leq 3\ \ \\ \end{matrix} \right.\ \]
\[Ответ:x \in \lbrack - 2;3\rbrack.\]